For more pluralistic critiques of colonialism: A response to Dunlap. (December 2021) - Ramirez, Jacobo; Böhm, Steffen
Abstract: In accordance with critical reflective thinking on colonialisation, we respond to Dunlap's critical remarks on our article by deconstructing some of the themes presented in the debate on internal colonialism in the context of large-scale wind energy developments in the Isthmus of Tehuantepec, Mexico. We return to a historical conceptualisation of internal colonialism as it pertains to a continuation of colonial-like dynamics – oppression, repression, violation and exploitation of vulnerable people – within a country, which is important for our discussion on energy justice, particularly cognitive justice, as the colonial-like dynamics of economic transactions between economically motivated indigenous people and private investors with the support of elite actors – which we term transactional colonialism – have repercussions for vulnerable people and indigenous livelihoods. We hope that our perspective will contribute to the global discussion of the socio-ecological impacts of large-scale wind energy developments and green transitions more generally.